2017
DOI: 10.1097/pcc.0000000000001248
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Chest Compressions During Sustained Inflations in a Perinatal Asphyxial Cardiac Arrest Lamb Model

Abstract: Objective Continuous chest compressions (CCCs) are more effective during resuscitation in adults. Sustained inflation (SI) rapidly establishes functional residual capacity in fluid-filled lungs at birth. We sought to compare the hemodynamics and success in achieving return of spontaneous circulation (ROSC) in an asphyxial cardiac arrest lamb model with transitioning fetal circulation and fluid-filled lungs between subjects receiving CCCs during SI and those receiving conventional 3:1 compression-to-ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Combining CC with SI (n = 7) did not improve recovery in lambs compared to 3:1 C:V CPR (n = 6) [41]. The main difference between the piglets and lambs were that the pigs were post-transitional, whereas the lambs were examined during cardiopulmonary transition.…”
Section: Continuous Chest Compression Superimposed By a Sustained Infmentioning
confidence: 92%
See 1 more Smart Citation
“…Combining CC with SI (n = 7) did not improve recovery in lambs compared to 3:1 C:V CPR (n = 6) [41]. The main difference between the piglets and lambs were that the pigs were post-transitional, whereas the lambs were examined during cardiopulmonary transition.…”
Section: Continuous Chest Compression Superimposed By a Sustained Infmentioning
confidence: 92%
“…In asphyxiated piglets and lambs, different CC approaches have been investigated as alternatives to the standard 3:1 C:V ratio including different C:V ratios 2:1 [33], 4:1 [33], 9:3 [34], and 15:2 [35], continuous CC with asynchronous ventilations (CCaV) [36,37] at different CC rates (90/min, 100/min and 120/min) [38], and continuous CC with sustained inflation (SI) [39][40][41] at different CC rates [42] and SI duration [43].…”
Section: Cerebral Blood Flow During Different Ways Of Performing CCmentioning
confidence: 99%
“…These studies suggest that during neonatal CPR, different C:V ratios do not improve outcomes and might not be the optimal CC approach in newborn infants. In comparison with the recommended 3: 1 C:V, combining CC with sustained inflation has been shown to be more effective in improving ROSC in piglets [15, 22-24], but not in lambs [25]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the study by Schmölzer et al used a CC rate of 120/min (in the CC + SI group), which is higher than the currently recommended CC rate of 90/min, which could have also added to the improved outcomes. A recent study using a perinatal cardiac arrest lamb model with transitioning fetal circulation and fluid filled lungs reported that CC + SI is as effective as 3:1 C:V ratio in achieving ROSC ( 27 ).…”
Section: Rational For Using Continuous Ccs With Simentioning
confidence: 99%